Dyspnea induced by hemidiaphragmatic paralysis after ultrasound-guided supraclavicular brachial plexus block in a morbidly obese patient. Issue 2 (14th January 2022) - Lang, Jiaxin; Cui, Xulei; Zhang, Jia; Huang, Yuguang
Abstract : Supplemental Digital Content is available in the text Abstract: Rationale: Hemidiaphragmatic paralysis (HDP) is a frequent complication of the brachial plexus block, caused by unintentional blockade of ipsilateral phrenic nerve. HDP did not rise enough alarm and attention to most anesthesiologists, because most patients with no coexisting comorbid diseases are asymptomatic and able to tolerate it. However, it may cause severe respiratory complication for patients with preexisting compromised cardiorespiratory function. Patient concerns: A 67-year-old woman with morbidly obesity was planned to receive opening reduction and internal fixation of right humeral shaft fracture under regional anesthesia considering less respiratory and cardiovascular system interference compared with general anesthesia. Diagnoses: After ultrasound guided supraclavicular brachial plexus block, the patient developed severe hypoxia and hypercapnia.Unintentional block of phrenic nerve and diaphragm paralysis was diagnosed by diaphragm ultrasound, which was considered as the main reason of severe hypoxia. Interventions: It led to a conversion from regional anesthesia to general anesthesia with endotracheal intubation for patient's safety and smooth operation. Outcomes: The unintentional phrenic nerve block leads to a prolonged ventilation time, length of stay in intensive care unit and length of stay in hospital. Lessons: This case report highlights the risk of diaphragm paralysis in morbidly obese patients. Though new diaphragm sparing brachial plexus block (BPB) methods were developed intended to reduce the risk of HDP, no approaches could absolutely spare phrenic nerve involvement. Therefore, clinicians should always consider the risk of HDP associated with BPBs. For each individual, a detailed preoperative evaluation and sufficient preparation are paramount to avoid serious complications.